2010
DOI: 10.1016/j.medin.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidad pulmonar por hiperoxia

Abstract: Resumen La ventilación mec anica es capaz de producir y agravar el daño pulmonar y contribuir a la aparición de fracaso multiorg anico. Uno de los mecanismos descritos es la hiperoxia alveolar que, en modelos experimentales, conlleva una producción de radicales libres de oxígeno (O 2 ) que exceden las posibilidades de defensa celular, y dan lugar a inflamación, a sobreexpresión gen etica y a daño celular directo con fenómenos de necrosis y apoptosis. Los hallazgos en humanos no son tan concluyentes, sí est a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
3
0
4
Order By: Relevance
“…Interestingly, responders to this test had a hospital mortality of 14%, whereas nonresponders had a mortality of 91% (p <0.01). We evaluated the possibility that myocardial dysfunction was not fully reversible by conducting stress echocardiography in a group of 33 patients (28 septic patients) with mean age 41 years [173]. One month after hospital discharge, all the echocardiographic alterations had normalised.…”
Section: Diagnosismentioning
confidence: 99%
“…Interestingly, responders to this test had a hospital mortality of 14%, whereas nonresponders had a mortality of 91% (p <0.01). We evaluated the possibility that myocardial dysfunction was not fully reversible by conducting stress echocardiography in a group of 33 patients (28 septic patients) with mean age 41 years [173]. One month after hospital discharge, all the echocardiographic alterations had normalised.…”
Section: Diagnosismentioning
confidence: 99%
“…Numerous studies have also shown that oxygen radicals, generated primarily in response to hyperoxia, contribute to the development of hyperoxiainduced ALI, thus, implicating the presence of excessive reactive oxygen species (ROS) in the pathogenesis of ALI (Papaiahgari et al 2004;Cho et al 2006;Gore et al 2010). The development of future treatments will require detailed investigation of therapeutic modality effectiveness in new-born patients, including assessment of cytokine network imbalances corrections, inhibition of inflammatory cells, regulation of inflammatory factor release, and elevation of antioxidant capacity (Gordo-Vidal et al 2010).…”
mentioning
confidence: 99%
“…En la revisión integrativa se encontró una variedad de cuidados de enfermería enfocados a atender la necesidad de oxigenación, la cual está estrechamente relacionada con los procesos de respiración, ya que el aporte de oxígeno es fundamental en la homeostasis del sistema cardio-respiratorio. Pan et al (2020), implementaron una estrategia de oxigenoterapia que mejoró los resultados clínicos de los pacientes críticos (29), considerando que el oxígeno puede causar daño si se administra de forma inapropiada (35)(36). La hipoxemia es frecuente en pacientes con enfermedad por COVID-19, por lo que Perkins et al (2021), describieron recomendaciones dirigidas a enfermeros que brindan cuidado en la primera línea de atención (30).…”
Section: Discussionunclassified